EXAMINATION OF THE SUNGKAI’S YOUNG LEAF EXTRACT (Peronema canescens) AS AN ANTIPIRETIC, IMMUNITY, ANTIPLASMODIUM AND TERATOGENITY IN MICE (Mus.muculus) - Agus Martono Hadi Putranto (International Journal of Science and Engineering, 2014)
The research of examination extract sungkai’s young leafs as an antipyretic, immunity, anti plasmodium and teratogenity in mice (Mus. Muculus) has been done. The aims of this research is examinations in infusa effectiveness extract of the young leafs in mice (Mus. Muculus). The object of this research used 50 males Webster’s species mice has 7 – 8 week olds, averages 30 gram in weight. Mice are divided into 5 groups in examination for antipyretic. Mice has been introduced the DPT-HB fever before. The first group as a negative control treated a pure water, second group as a positive control treated a paracetamol 1.08 mg/Kg w/w and rest of groups treated a young sungkai’s extract leafs in the concentration of 0.186 mg/Kg w/w, 0.375 mg/Kg w/w and 0.5625 mg/Kg w/w respectively. Measurements of the temperature toke in the duration of 30, 60, 90 and 120 minutes. Furthermore, in the immunity examination, mice also divided into 5 groups, first as a negative control treated a pure water, second group as a positive control treated 0.07 mg/Kg imunos w/w and respectively for the rest groups treated with young sungkai’s extract leafs in the concentration of 0.186 mg/Kg w/w, 0.375 mg/Kg w/w and 0.5625 mg/Kg w/w. These treatments held in gavage system with the duration at 24 hours. In examination amount of the leukocyte number, toke from the tail of the mice, has a result the dosage in 0.5625 mg/Kg w/w extract’s young leafs of sungkai could be decrease the temperature 29%, it is better than paracetamol treatment which could be decreased only 26% of temperature. In addition, for the immunity examination, the best dosage of the young sungkai’s extract leafs is 0.567 mg/Kg w/w, which It can increase 36% amount of the leukocyte number. This dosage is better than the positive control by using Imunos, which is can increase only 23% of the temperature.